Word Formation in the English and Uzbek Languages (Journal of Pedagogical Inventions and Practices, 2022)
In this given article we analyzed the linguistic features of word formation in English and in Uzbek.Word formation is the process that serves to enrich the content of the language dictionary on a regular basis. There are some similarities and differences between word formation system of Uzbek and English. In the article we tried to study some ways of word formation and to clarify the theme we presented a lot examples.